Science Experiment Book Validated for Interpersonal Intelligence Development - Zalika Ayu Lestari Salman Naukoko; Andi Agusniatih; Hesti Putri Setianingsih; Besse Nirmala (Academia Open, 2026)
General Background: Early childhood education requires learning media that not only support cognitive development but also stimulate multiple intelligences, particularly interpersonal intelligence, which is essential for children’s social growth. Specific Background: Science learning activities in early childhood settings are often limited to teacher-centered approaches and lack instructional media that encourage active social interaction among children. Knowledge Gap: There is limited availability of science-based instructional media specifically designed to stimulate interpersonal intelligence through collaborative experimental activities for children aged 5–6 years. Aims: This study aims to develop a science experiment book as an instructional medium to stimulate multiple intelligences, particularly interpersonal intelligence, among children aged 5–6 years at TK Idhata Beka. Results: Using a Research and Development approach involving needs analysis, product design, expert validation, and limited field trials, the findings show that the developed science experiment book was categorized as very feasible in terms of media and content quality, and its implementation led to improvements in children’s interpersonal abilities, including cooperation, communication, and peer interaction during science-based experimental activities, indicating that the science experiment book has strong potential as an effective learning medium for supporting the development of interpersonal intelligence in early childhood education. Highlights: Expert appraisal classified the developed learning resource as very valid in content and media aspects. Group-based experimental sessions increased children’s peer dialogue and shared task completion. Structured hands-on activities supported observable progress across social interaction indicators. Keywords: Science Experiment Book, Multiple Intelligences, Interpersonal Intelligence, Early Childhood.